A Case of Severe Asymptomatic Aortic Coarctation in an Adult Female - Spyros Tsikrikas; Charalampos Charalampous; Konstantinos P. Letsas (Case Reports in Cardiology)
Coarctation of the aorta is typically a disease of childhood and early adulthood, and there is a reduced life expectancy in patients who have not undergone correction. Survival to older age is rare, due to severe cardiovascular complications. We describe the case of a woman first diagnosed with coarctation of aorta at an advanced age.